Lopping Studies on Prosopis cineraria - Srivastava, J. P. L. (Indian Forester, 1978)
The various aspects like season and intensity of lopping of Prosopis cineraria have been briefly reviewed. Studies conducted ar Neembi-Dullot reserved forest, Mohindergarh, Haryana has indicated that annual lopping of trees results in maximum forage yeild without detriment to their growth. It has also been observed that yeild of forage from trees below 45 cm girth is significantly low, thereby suggesting a lower girth limit for the trees to be lopped.